Case report: Scapulohumeral arthrodesis in a reindeer - Hankins, Kimery L.; Reed, Shannon K.; Ida, Keila K.; Watkins, Jeffrey P.; White, Sarah A. (Frontiers in Veterinary Science, 2023)
This case report describes the anesthetic, surgical, and postoperative management of scapulohumeral arthrodesis in a juvenile reindeer with severe lameness due to a chronic proximal humeral fracture and scapulohumeral luxation. The reindeer was managed with prolonged stall confinement and physical therapy and 9 months postoperatively was walking and bearing weight equally when standing. This case demonstrates that comparative techniques from other veterinary species coupled with considerations for reindeer anesthesia can be successful in restoring functional soundness after scapulohumeral arthrodesis.